Enforcement Of Regional Regulation Number 2 Of 2020 Concerning Public Order And Community Peace - Rasmaladewi; Rizki Mustika Suhartono; Hadi Supriyanto (Lembaga Penelitian dan Pengabdian Masyarakat, 2024)
To foster stability, order, and peaceful conditions in society, as well as to instill a sense of discipline and habitual behavior among individuals in South Buton Regency, the South Buton Regency Regional Regulation Number 2 of 2020 concerning Public Order and Community Peace was established. This regulation underscores the significance of community participation in enhancing various aspects of life, including knowledge, economy, social structures, environment, and politics. Active engagement from all members of society is essential in creating a safe and comfortable environment. However, the effectiveness of this regulation is hampered by the lack of public awareness and understanding, primarily due to insufficient dissemination of information. As a result, many community members are unaware that they may be violating the regulation, leading to inadvertent non-compliance. The absence of proper socialization efforts from relevant authorities means that the public does not receive necessary information or warnings about the prohibitions outlined in the regulation. This gap in communication and education is a critical factor contributing to the lack of adherence to the regulation and underscores the need for more robust public outreach and education initiatives. By improving socialization and awareness efforts, the authorities can ensure that the community is better informed, which will enhance compliance and ultimately contribute to a more orderly and peaceful society.